Renal function following fistulography in patients with advanced chronic kidney disease. (July 2013) - Hill, Marlene; Mor, Maria K.; Travis, Lesli; Ward, Tina; Palevsky, Paul M.; Ramkumar, Mohan; Weisbord, Steven D.
Abstract Background/aims: Contrast-induced acute kidney injury (CIAKI) is associated with an accelerated progression of underlying chronic kidney disease (CKD). We sought to characterize the rate of loss of kidney function following fistulography in patients with advanced CKD. Materials/methods: We identified all patients with stage 4 or 5 non-dialysis-dependent CKD who underwent fistulography with iodinated contrast for non-maturing arteriovenous fistulae between 1 January 2010 and 30 November 2011. We recorded all eGFR values measured during the 6 months prior to and 6 months following the procedure, the volume and type of contrast, use of intravenous fluid and N-acetylcysteine (NAC), and timing of dialysis initiation following the procedure. We used mixed linear regression with random effects to compare the composite slope of decline in eGFR prior to and following fistulography. Results: Overall, 27 patients underwent a total of 44 fistulograms. The mean age of the patients was 66 years and mean baseline eGFR was 16.7 ± 5 mL/min/1.73 m2. Patients received a median volume of contrast of 12 mL [IQR 10–20]. None of the patients initiated acute dialysis within weeks following the procedure. In unadjusted analyses, there was no statistically significant change in the rate of decline in eGFR following fistulography compared to pre-procedure (0.14 mL/min/month versus −0.14 mL/min/month, p = 0.11). In analyses that adjusted for procedural, demographic and clinical variables, the decline in eGFR following fistulography was not statistically different than before the procedure (0.15 mL/min/month versus −0.14 mL/min/month, p = 0.11). Conclusions: Fistulography with small volumes of iodinated contrast in patients with advanced CKD does not result in more rapid progression of underlying CKD.